2007
DOI: 10.1080/10408440601123545
|View full text |Cite
|
Sign up to set email alerts
|

The Hypothalamic-Pituitary-Thyroid (HPT) Axis in Frogs and Its Role in Frog Development and Reproduction

Abstract: Metamorphosis of the amphibian tadpole is a thyroid hormone (TH)-dependent developmental process. For this reason, the tadpole is considered to be an ideal bioassay system to identify disruption of thyroid function by environmental contaminants. Here we provide an in-depth review of the amphibian thyroid system with particular focus on the role that TH plays in metamorphosis. The amphibian thyroid system is similar to that of mammals and other tetrapods. We review the amphibian hypothalamic-pituitary-thyroid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 260 publications
2
46
0
Order By: Relevance
“…TRα also was found in all of the 14 tissues examined during embryonic and posthatch development, although the presence of TRβ was restricted to brain, eye, lung, yolk sac, and kidney, and the patterns of its expression differed with developmental age (Forrest et al, 1990). Overall, these data suggest general early developmental roles for TRα and specific developmental roles for TRβ, as is the case for this isoform in other vertebrate classes (see Zoeller, 2007a;Fort, 2007). Additional evidence that TRα is important in very early embryonic development comes from the studies of Flamant and Samarut (1998), who found a low level of TRα expression initially followed by an increase in expression in neuroectoderm during neurulation in the chicken embryos prior to incubation.…”
Section: Thyroid Hormone Actionmentioning
confidence: 70%
“…TRα also was found in all of the 14 tissues examined during embryonic and posthatch development, although the presence of TRβ was restricted to brain, eye, lung, yolk sac, and kidney, and the patterns of its expression differed with developmental age (Forrest et al, 1990). Overall, these data suggest general early developmental roles for TRα and specific developmental roles for TRβ, as is the case for this isoform in other vertebrate classes (see Zoeller, 2007a;Fort, 2007). Additional evidence that TRα is important in very early embryonic development comes from the studies of Flamant and Samarut (1998), who found a low level of TRα expression initially followed by an increase in expression in neuroectoderm during neurulation in the chicken embryos prior to incubation.…”
Section: Thyroid Hormone Actionmentioning
confidence: 70%
“…However, rates of development were not measured in these animals because the focus of the study was to investigate UVBR avoidance behavior and survival in exposed tadpoles. Because effects of UVBR on the thyroid system in amphibians remain to be fully explored and because the brain-pituitary-thyroid axis is well conserved among vertebrates (Crespi and Denver 2005;Fort et al 2007), examining previous findings on the effects of UVBR on the thyroidal axis in other organisms may provide insight into potential impacts on amphibians.…”
Section: Potential Disruption Of the Endocrine Control Of Amphibian Dmentioning
confidence: 99%
“…To assess how environmental stressors such as UVBR affect amphibian development, it is important to understand the endocrine axis controlling amphibian metamorphosis. We provide a brief overview of the hormonal pathways involved, which have been extensively described by several authors (e.g., Dodd and Dodd 1976;Denver 1996;Tata 1996Tata , 2006Shi 2000;Shi and Ishizuya-Oka 2001;Denver et al 2002;Brown 2005;Brown and Cai 2007;Fort et al 2007). …”
Section: Potential Disruption Of the Endocrine Control Of Amphibian Dmentioning
confidence: 99%
“…Xenopus laevis is an amphibian species widely used as a suitable amphibian model for thyroid disruption research (Fort et al 2007;Huang et al 2005), and has been introduced as a model to study effects of endocrine-active compounds on development and sexual differentiation. The amphibian metamorphosis in X. laevis provides a well-studied, thyroid-dependent process which responds to substances active within the HPT axis, and it is the only existing assay that detects thyroid activity in an animal undergoing morphological development.…”
Section: Introductionmentioning
confidence: 99%